A Study of Several Water Purification Techniques (International Journal of Innovative Research in Computer Science & Technology, 2022)
Current article provides an overview of  current water purification, filtration methods, &  technologies. water purification is primarily addressed for  a sensitive reason: it is one of most important sources of  survival for all living things. water may be found in various  forms on earth's surface, & lakes & rivers provide a  significant quantity of drinking water. all living things  need water to survive, but humans require filtered water  that is high in minerals & salts. lack of germs & disease causing microbes, dissolved metal ions, & heavy  contaminants is referred to as pure water. drinking water  must be not only pure but also healthful in order to be fully  functional. some water purification methods use hazardous  polymers & terrible chemical compositions. n-current  methods for water purification & filtration were upgraded  & incorporated into nanotechnology & polymers. reverse  osmosis is foundation for any purification process that  employs semipermeable membranes with ultra, micro, &  nano porous membranes to remove germs,  microorganisms, minerals, & salts. if consumed over an  extended period of time, this ro-processed water may cause  sickness. to overcome need to add minerals & salts to  water, fiber composites & mineral cartridges were  developed. all of se water purification methods, as well as  use of fiber composites & polymer membranes, are  discussed in this article, along with flaws that may do a lot  of harm to humanity.
Keywords: Chlorination; Coagulation; Filtration; Purification; water